Insights into myxozoan composition and physiology revealed by histochemical properties of myxospores. Issue 5 (23rd March 2020) - Stilwell, Justin M.; Griffin, Matt J.; Rosser, Thomas G.; Mohammed, Haitham H.; Sidor, Inga F.; Camus, Alvin C.
Abstract: Myxozoa (phylum Cnidaria) are a diverse group of metazoan parasites that predominately infect fish. Little is known regarding the composition and physiology of their myxospore life stage. The objective of this work was to investigate the composition of myxospores and extrasporogonic stages of nine myxozoan species infecting various teleost fish using histochemical staining techniques. Thirty histochemical stains were applied to formalin‐fixed, paraffin‐embedded tissues processed routinely for light microscopic evaluation. The polar capsules were the most consistent stain target across the taxa examined. Polar capsule staining with Alizarin red, von Kossa and methyl green‐pyronin suggests the presence of intracapsular calcium and phosphate, which may contribute to polar filament discharge or pathogenesis of host invasion. The shell valves and suture lines of most myxozoans were stained with Luna and phosphotungstic acid haematoxylin stains, consistent with the presence of chitin and microfibrils, respectively. Vacuoles were consistently highlighted by diastase‐susceptible periodic acid‐Schiff and Grocott's methenamine silver staining, indicating glycogen. Other histochemical stains exhibited inconsistent staining across the taxa, suggesting differences in myxospore composition potentially reflective of physiologic variations and tissue tropisms. This work provides some information on conserved features and taxa‐associated composition of myxospores and lends insight into myxozoan physiology and host–parasite interactions.